The A-Z encyclopedia of food controversies and the law - Williams, Elizabeth M. (Elizabeth Marie) 1950-; Carter, Stephanie J.; Gale Group (Santa Barbara, Calif. Greenwood/ABC-CLIO, 2011)
Covering food and law, this encyclopedia surveys laws related to organics, obesity, and fair trade.
v. 1. A-P -- v. 2. R-Z. Pt. 1. Court cases -- United States v. Fior d?Italia, Inc. (2002) -- Commack Self-Service Kosher Meats, Inc v Weiss (2002) -- Pelman, et al. v. Mcdonald?s Corporation (2003) -- Amended complaint in Pelman, et al. v. Mcdonald?s Corporation (2003) -- Pelman, et al. v. Mcdonald?s Corporation, Court of Appeals (2005) -- Arnett, et al. v. Snyder (2001) -- North American Cold Storage Co. v. City of Chicago (1908) -- United States v. Park (1975) -- Pt. 2. Laws, regulations, and regulatory review -- In the matter of McCormick & Company, Inc. (2000) -- California Organic Products Act of 2003 -- Twenty-Eight Hour Law of 1873, as amended in 1994 -- Senate bill, introduced into the 111th Congress, amending the Food, Drug, and Cosmetic Act (2009) -- Bill AB 1437 introduced into the California legislature dealing with shelled eggs (2009) -- U.S. Code Sections 341 and others -- Code of Federal Regulations regarding cheese and cheese food -- Enabling Act of the zoning laws of the City of Boston (1956), as amended -- Pt. 3. Uruguay Round Agreement on agriculture (1998) -- World Trade Organization ministerial conference decision (2001) -- World medical assembly declaration on hunger strikers (1992).
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction. New York : Gale, 2011. Available via World Wide Web through Gale Virtual Reference Library.
Keywords: Food law and legislation -- United States; Electronic books